2020
DOI: 10.1177/0031721720970702
|View full text |Cite
|
Sign up to set email alerts
|

How teachers experienced the COVID-19 transition to remote instruction

Abstract: The COVID-19 viral pandemic affected all facets of life, including schooling. In March 2020, schools abruptly ended face-to-face instruction and transitioned to emergency remote instruction. David Marshall, David Shannon, and Savanna Love surveyed teachers nationally between mid-March and early April 2020 to understand their experiences during this time. Teachers found all aspects of teaching more challenging during remote instruction and shared a range of experiences related to training opportunities, barrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
180
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(199 citation statements)
references
References 1 publication
6
180
0
13
Order By: Relevance
“…The difficulties teachers faced are in line with the results of this study. Similar to highlighting inexperience, Marshall, et al (2020), indicate that the majority of teachers (92.4%) have not experienced online teaching before ERT and very few of them have had a quality training on this subject. Gares, et al (2020) express that although there were no problems in terms of technology and software, not being competent in how to use technology on the part of students and teachers led to problems.…”
Section: Ways To Overcome the Difficulties Experienced During Emergency Remote Teaching Periodsupporting
confidence: 52%
See 1 more Smart Citation
“…The difficulties teachers faced are in line with the results of this study. Similar to highlighting inexperience, Marshall, et al (2020), indicate that the majority of teachers (92.4%) have not experienced online teaching before ERT and very few of them have had a quality training on this subject. Gares, et al (2020) express that although there were no problems in terms of technology and software, not being competent in how to use technology on the part of students and teachers led to problems.…”
Section: Ways To Overcome the Difficulties Experienced During Emergency Remote Teaching Periodsupporting
confidence: 52%
“…They explained these difficulties as "internet connection (65%), technical issues (15%), overloading of conferencing tools (10%), and passive learners (10%). " Marshall, et al (2020) suggest that some teachers did not have reliable internet access at home. Also, 57,2% of the participants in their study mentioned that at least onefourth of their students did not have access to broadband internet outside school and even if they had, these students did not have appropriate tools to study online.…”
Section: Ways To Overcome the Difficulties Experienced During Emergency Remote Teaching Periodmentioning
confidence: 99%
“…Schools then reopened online, usually after 2 weeks, though for certain large American school districts this took far longer. Since few U.S. teachers had online teaching experience, this did not go well (Hess, 2020;Marshall, Shannon, & Lee, 2020). Most other countries also closed physical schools in March and reopened online shortly thereafter.…”
Section: Non-american Responses To Covid-19mentioning
confidence: 99%
“…A few studies have reported some of the challenges that teachers have experienced in relation to ERT. Low familiarity with online teaching has been reported to be one of the predominant elements overwhelming teachers, at least in the initial stage of ERT [3][4][5][6]. In the process of moving their whole work practice online, many teachers found that all job functions became more challenging [6], not only in terms of the increased workload relating to teaching preparation but also in terms of engaging students and assessing student learning outcomes [7].…”
Section: Introductionmentioning
confidence: 99%